(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
In this article, we carried out a comparative analysis of competition and monopolistic activity. The differences between monopoly and oligopoly, types of monopolistic activity, types of competition, market indicators, properties of competition, positive and negative features of competition, the concept of competitiveness are considered; public authorities authorized to identify and limit monopolistic activity in the economy; methods of combating monopolistic activity used by the state in the modern world.